Risk factors associated with early childhood caries: A bibliometric analysis - Melissa Pinella-Vega; Julio Romero-Gamboa; John E. Gallego-Ramírez; Pablo A. Millones-Gómez; Alejandro Valencia-Arias (GarVal Editorial Ltda., 2024)
Context: Early childhood caries (ECC) is a significant oral health problem affecting children worldwide. Its consequences can range from pain and infection to impact on children's quality of life. Research on risk factors associated with ECC is evolving but shows gaps and inconsistencies. Aims: To examine research trends on risk factors associated with early childhood caries in the Scopus and Web of Science databases. Methods: A methodology based on the PRISMA 2020 declaration was used, focusing on a systematic bibliometric review. Results: The results showed a significant increase in scientific interest in ECC, especially in 2021 and 2022, with a 98.87% increase in publications. Countries such as India and the United States were leading the research, and current thematic trends lean towards oral hygiene practices and survival analysis. Conclusions: The evolution of the field suggests a focus on emerging areas and adaptability to the changing needs of affected populationss.